Effect of Different Feeding Regimes on Feed Intake, Body Weight and Body Condition Score of Crossbred Cows - Islam, Md. Manzarul; Shah, Shailesh V.; Pandya, Paresh R.; Lunagariya, Pravin M. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study was conducted from 45 d prepartum to 300 d post-partum on 18 crossbred cows, distributed into three treatment groups  comprising six animals in each group. Animals of the T1 (Farmers’ feeding) group were maintained as per the feeding regime, followed by  small and marginal farmers. Animals of T2 (Modified feeding)group were fed with scientific interventions using resources available with  farmers. Animals of the T3 (Farm feeding) group were fed as per feeding followed at Livestock Research Station. Average DMI both on kg/ animal/d and kg/100 kg b.wt. was significantly (p
Keywords: BCS; Body weight; Crossbred cows; Feed intake; Feeding regimes